Virtual politics : faking democracy in the post-Soviet world - Wilson, Andrew 1961- (Yale University Press, 2005)
Introduction -- 'Active measures' : a Russian tradition -- Politics as virtuality in the post-soviet world -- The 'political technologist' : Machiavelli as corporate adviser -- 'Administrative resources' -- Politics as theatre : disguising the state holding company -- How many towers in the Kremlin? the 'many-layered pie' -- Dishing the opposition -- Inventing the opposition : Kremlin parties -- Inventing the opposition : virtual communists -- Conclusions.